Pendampingan Pembuatan NIB Dan P-IRT Pada UMKM Kelurahan Gunung Anyar Tambak RW 01 Surabaya - Anisah Aprilia Garciah; Dalilah Edenya Zata Yumni; Firdi Ihza Rochman; Kirana Azzahra Putri; Dhian Satria Yudha Kartika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Most of the residents of RW 01 Gunung Anyar Tambak Village, Gunung Anyar District, Surabaya, make a living as fishermen. Shrimp paste is the main product for micro, small, and medium enterprises (MSMEs) in the area, made from fish and shrimp. The sale of shrimp paste MSMEs in the area is limited to promotion through WhatsApp or simply word of mouth, so there is a need to develop MSMEs to improve the local economy. In the activity of the SDG’s KKNT Work Program for Group 1 of Gunung Anyar Tambak Village, MSMEs are developed by obtaining NIB (Business Identification Number) and PIRT (Food and Beverage Production Permit). By obtaining NIB, the business will be legally guaranteed to meet the requirements for Business and Commercial or Operational Permits. The function of PIRT itself is to increase customer confidence, as product safety and quality are ensured.